(untitled) (Development Engineering Conferences Center Articles Database, 2025)
This study explores the dynamics, challenges, and outcomes of land reform in various developing regions, with a particular focus on Africa, Asia, and Latin America. The primary objective is to assess the effectiveness of redistributive land reforms in reducing rural inequality, promoting agricultural productivity, and supporting sustainable development. By analyzing historical and contemporary cases—such as those of Mexico, India, Iran, Kenya, and South Korea—the study reveals that successful land reforms typically involve state intervention, redistribution of land to the rural poor, and structural changes in power relations. Results indicate that while some reforms led to notable gains in equity and productivity, others were undermined by political resistance, inadequate implementation, and economic liberalization. Empirical comparisons show higher yields and employment intensity on smallholder farms following reform. However, reforms also face challenges such as land fragmentation, tenure insecurity, and the marginalization of subsistence farmers. The study concludes that equitable land reform remains a vital but underutilized tool for rural development. It calls for integrated policy frameworks that include land redistribution, institutional support, and agrarian justice to address deep-rooted inequalities and support long-term socio-economic and ecological sustainability.